Problems associated with a robot laser cell used for hardening - Babič, Matej (Materiali in tehnologije, 2013)
Laser hardening is a surface-hardening process. It is used exclusively on ferrous materials suitable for hardening, including steel and cast iron with acarbon content of more than 0.2 %. This article describes robot laser hardening, the results of previous work, research and experience with robot laser hardening. The second part of the paper describes the problems associated with robot laser hardening at different angles. We wanted to find the impact of the angles on the hardness of the material. Therefore, we directed the laser beam at different angles, including perpendicular, in the process of hardening. We made test patterns of a standard label on the materials of DIN standard 1.2379.
Keywords: hardening; površinsko utrjevanje; robot laser; obdelava materiala; parameters; kaljenje; robot; laser; parametri